Hydrogen Bonded Networks with Variable Functionalized Netpoints : a Probe of Mesophase Stability - Schieffer, Phillip J.; Hammers, Matthew D. (My University, 2010)
A series of halogen-bonded supramolecular networks based on rigid bispryidyls, non-meosgenic tetrapyridyls and bis(4-iood-2,3,5,6-tetraflouophenoxyl)-1,10-decane was synthesized. All complexes were analyzed bor liquid crystalline characteristics.
Halogen Bonded Liquid Crystalline Networks
Color poster with text and diagrams.
Keywords: Liquid crystals--Research; Hydrogen bonding--Research; Supramolecular chemistry; Posters; Halogens